Biodegradation of 1,1,1-Trichloro-2,2-bis (4-chlorophenyl) ethane (DDT) by Mixed Cultures of White-Rot Fungus Ganoderma lingzhi and Bacterium Pseudomonas aeruginosa - Erly Grizca Boelan; Adi Setyo Purnomo (Bogor Agricultural University, Indonesia, 2019)
This study investigated the biodegradation of 1,1,1-trichloro-2,2-bis (4-chlorophenyl) ethane (DDT) by mixed cultures white-rot fungus Ganoderma lingzhi BMC 9057 and bacteria Pseudomonas aeruginosa. Cultures bacteria P. aeruginosa with various volumes 1, 3, 5, 7, and 10 ml (1 ml ≈ 1.53 x 109 bacteria cells/ml cultures) was added into 10 ml G. lingzhi cultures for degrading DDT. After 7 d incubation, DDT was degraded about 100% with addition of 5, 7, and 10 ml of P. aeruginosa culture into G. lingzhi. Two metabolites; 1,1-dichloro-2,2-bis (4-chlorophenyl) ethane (DDD) and 1-chloro,2-2-bis (4-chlorophenyl) ethylene (DDMU) were detected from mixed cultures G. lingzhi and P. aeruginosa as metabolite products of DDT. This research indicated that mixed cultures of whiterot fungus G. lingzhi and P. aeruginosa could be used to degrade DDT.